Agriculture on the road to industrialization - Mellor, John W. (International Food Policy Research Institute, 1995)
Solving the poverty problem in low-income countries requires rapid growth in output, income, and employment. An effective way to realize such growth is raising productivity in the large agriculture sector. Agriculture is important because it employs so much of the labor force in the early stages of development. It has the capacity to exploit productivity-increasing technological innovations that make large net additions to national income and hence to purchasing power. Rising farm incomes are spent largely on labor-intensive products of the rural sector, boosting demand where it does the most good in generating further increases in employment. Agriculture on the Road to Industrialization tells how agricultural growth can be accelerated so as to have a major impact in generating demand for output from the labor-intensive rural sector. It includes case studies from Thailand, Punjab (India), the Philippines, Kenya, Costa Rica, Colombia, and Argentina.